2018
DOI: 10.1016/j.rboe.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Total knee and hip arthroplasty: the reality of assistance in Brazilian public health care

Abstract: ObjectiveTo analyze the number of hospital permits for total knee arthroplasty (TKA) and total hip arthroplasty (THA) in Brazil between 2008 and 2015, and correlate them with regional, national, and international demographic and epidemiological aspects.MethodsData on demographics, economic level, and TKA and THA were obtained from the website of the Ministry of Health/DATASUS, Brazilian Institute of Geography and Statistics, and the National Health Agency to assess the assistance provided by the Public Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 19 publications
1
20
1
13
Order By: Relevance
“…The study also found a higher frequency of infection in patients with associated diseases, hospital stay of more than 6 days, surgical time of between 2 and 3 hours, use of prophylactic antibiotics and in patients classified as type II in the classification of ASAPS. However, in this study the results were not significant for hospital stays higher or lower than 5 days, and the other variables studied (duration of surgery, associated comorbidities, use of prophylactic antibiotic, ASAPS classification, side of operated knee, age and length of hospital stay) were also not significant and determinant factors for increased prevalence of infection, contrasting with other studies [2]- [12] [14]- [21].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The study also found a higher frequency of infection in patients with associated diseases, hospital stay of more than 6 days, surgical time of between 2 and 3 hours, use of prophylactic antibiotics and in patients classified as type II in the classification of ASAPS. However, in this study the results were not significant for hospital stays higher or lower than 5 days, and the other variables studied (duration of surgery, associated comorbidities, use of prophylactic antibiotic, ASAPS classification, side of operated knee, age and length of hospital stay) were also not significant and determinant factors for increased prevalence of infection, contrasting with other studies [2]- [12] [14]- [21].…”
Section: Discussioncontrasting
confidence: 99%
“…A small proportion of individuals diagnosed with arthroplasty infection maintained the result of negative culture and required empirical therapy, corroborating with other authors [10] [11] [12] [13] [14]. In this study the negative P. C. V. C. was also observed in patients of this present study and in these cases it is necessary to remove the implants [7]- [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There is a shortage of Brazilian arthroplasty data in the literature. Ferreira et al [17] showed date on public care but without data about costs. They have shown the reduction in LOS from 2008 to 2015 in Brazil, being the Midwest region of the country with the highest average of reduction (6.6 days), showing the heterogeneity of health care system in that country.…”
Section: Plos Onementioning
confidence: 99%
“…1,2 A ATJ pode ser definida como um procedimento cirúrgico de alta complexidade para o tratamento da artrose capaz de demonstrar dados satisfatórios e duradouros na melhora da dor, da qualidade de vida, e da função do paciente, bem como na correção de deformidades e instabilidades de origens relacionadas a processos degenerativos que comprometem a articulação do joelho. 3 Este procedimento apresenta excelentes resultados pós-operatórios em relação à sobrevida do implante, com índices de mais de 95% em pelo menos 10 anos de seguimento. 4 O desgaste do polietileno pode produzir detritos que influenciam na soltura dos componentes protéticos.…”
Section: Introductionunclassified